POTRET KETERAMPILAN PROSES SAINS SISWA DALAM PEMBELAJARAN IPA DI SD NEGERI 1 SUSUT - Darmayanti, Ni Wayan Sri; Sunarianingsih, Ni Luh Putu (Dharmas Education Journal (DE_Journal), 2024)
This study is motivated by the importance of understanding the extent to which students have science process skills, especially at the elementary school level, as one indicator of the effectiveness of science learning. The main problem studied in this study is the level of science process skills of fourth grade students at SDN 1 Susut. This study aims to find out in depth and quantitatively how these science process skills develop among 31 fourth grade students, and involves one fourth grade teacher who has an important role in the learning process. The research method includes the use of instruments in the form of questionnaires, interview guidelines, and documentation to collect relevant data. Each of these tools is very important to help in obtaining sources of information about science process skills. This data analysis method is carried out descriptively, and to measure the results of the student questionnaire, a Likert scale is used. The results of the study showed that based on the questionnaire data, the distribution of science process skills of grade IV students of SDN 1 Susut was as follows: 48.39% of students were included in the Very Good (SB) criteria, 38.71% in the Good (B) criteria, 9.67% in the Fairly Good (CB) criteria, and 3.22% in the Less Good (KB) criteria. Analysis of interviews with teachers revealed that although students' science process skills were already at a good level, further improvements were still needed to improve the quality of learning. This study is expected to be a foundation for further research and assist in the development of more effective learning methods in the future.